The Effect Of Hyaluronic Acid To Pain Intensity Rated By Face Pain Scale-Revised On Knee Osteoarthritis Patients - Hartono, Felicia Putri; Nugroho, Nunung; Isbandiati, Endang (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: Osteoarthritis (OA), is a chronic degenerative disease of joint associated with cartilage and joints. The most common symptoms of OA patients is joint pain that worsen in activity and relieved with rest. Hyaluronic acid (HA) injection is one of the treatment that used to relieved joint pain in OA patients. Aim : The purpose of this study was to determine the effect of HA injection to pain intensity on knee OA degree 2 and 3 patients in PHC Hospital Surabaya. Methods : Analytic research study design with retrospective cross-sectional study with purposive sampling technique. The respondents in this study were patients with knee OA degree 2 and 3 that had been failed with conservative therapeutics within 3 until 6 months and had been injected with HA in PHC Hospital in Surabaya. The number of respondents that have been collected that fulfill the inclusion and exclusion criteria were 46 respondents. Results : based on data analysis with Wilcoxon Signed Ranks Test there was an effect of HA injection in pain reduction on knee OA degree 2 and 3 patients (p = 0,00001). Conclusion : There is an effect of HA injection in pain reduction on knee OA degree 2 and 3 patients.